Development and Elaboration of a Model for Teaching Arabic Grammar Concepts Based on Simultaneous Thinking (A Grounded Theory Study with Delphi Validation) - Al-Janabi, Dheyaa Hussein Hashim; Mahmoudi, Mohamad Taghi; Al-Isawi, Mushreq Mohammed Mijwil; Saadatmand, Zohreh (Assessment and Practice in Educational Sciences, 2026)
The purpose of this study was to design and elaborate a model of “teaching grammatical concepts based on simultaneous thinking” for middle school students in Iraq. The study employed a mixed exploratory design. In the qualitative phase, grounded theory was applied using the systematic approach of Strauss and Corbin. The qualitative population consisted of experts in Arabic language teaching, curriculum design, and educational psychology. Through purposeful and snowball sampling, 18 experts were interviewed until theoretical saturation was achieved (from May to November 2023). To validate the identified components and indicators, the Delphi technique was implemented in two rounds with 30 experts. The consensus criteria were defined as a mean score above 4 and a standard deviation below 1. The Kendall’s coefficient of concordance was calculated as W = 0.85, indicating a high level of agreement among experts. In the qualitative analysis, 266 open codes were extracted and organized into axial categories. The core phenomenon, “teaching grammatical concepts based on simultaneous thinking,” was explained within a paradigmatic model consisting of four clusters: causal conditions, contextual conditions, intervening conditions, strategies, and consequences. The Delphi results confirmed the content and face validity of the model’s components. In conclusion, the proposed model provides an applicable and contextually grounded framework for redesigning Arabic grammar instruction at the middle school level and can contribute to enhancing linguistic skills and developing higher-order thinking among students.